TINGKAT EFEKTIFITAS DAN EFISIENSI SISTEM PEMBAYARAN TIKET NON TUNAI DALAM MENEKAN RESIKO KECURANGAN: STUDI KASUS DI KEBUN RAYA BALI - Tuwi, I Wayan; Ketut Mareni, Ni; Ayu Rai Sumariati, Dewa; Arnawa, I Putu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Digitizing public payment systems is a strategy to increase transparency and accountability in tourism services. This study evaluates the effectiveness and efficiency of cashless ticketing in reducing fraud risks at the Bali Botanic Gardens, Tabanan, using a quantitative approach with SEM-PLS. Data were collected from operational staff, management, and visitors, and tested for validity and reliability. The results indicate that cashless transactions play a significant role in reducing fraud opportunities through real-time recording, reduced manual intervention, and integrated financial reporting. Effectiveness is reflected in faster transactions, price transparency, and digital receipts, while efficiency is reflected in reduced administrative burdens, elimination of manual records, and optimization of human resources. Minimizing cash handling also strengthens audits and enhances institutional credibility. Statistical analysis revealed that 92.7% of the variability in fraud risk is influenced by effectiveness, efficiency, and operational conditions. QRIS, e-wallets, and mobile applications provide user-friendly solutions that also maintain financial integrity. Cashless systems are not simply technological innovations but part of structural reforms towards modern and accountable financial governance at tourist destinations.